Scenes of Ancient Rome. Evolution of a Project (LANX. Journal of the Scuola di Specializzazione in Beni Archeologici - Università degli Studi di Milano, 2011)
Presentation of the Project Scenes of Ancient Rome. The antiquity interpreted by contemporary arts edited by the Authors.
Keywords: rome; ancient art; contemporary arts; cinema; music; show